If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -5 = 7(x + -6) Reorder the terms: -5 + y = 7(x + -6) Reorder the terms: -5 + y = 7(-6 + x) -5 + y = (-6 * 7 + x * 7) -5 + y = (-42 + 7x) Solving -5 + y = -42 + 7x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + y = -42 + 5 + 7x Combine like terms: -5 + 5 = 0 0 + y = -42 + 5 + 7x y = -42 + 5 + 7x Combine like terms: -42 + 5 = -37 y = -37 + 7x Simplifying y = -37 + 7x
| 2x^4-x^3-9x^2+13-4=0 | | b-a=d | | p^3-3p+2=0 | | 18y+3y=6 | | s(4+p)=m | | X+3.2=7.5 | | 5(+4)=18-9 | | 3(4-6k)+1=-131 | | 3y+18y=6 | | 36x^2-48x+16=1 | | -5q-2(1-q)=-6q | | -2-1=-x-3 | | 3x+3x+15+2x+5=180 | | 6m+3=3m+3 | | 45b+2=-15b+3 | | h+9.1=5.3 | | 3+6=m | | 14x+7+20x+5=90 | | -3(6k+7)+6=93 | | 3(x+9)-2x+7=3(5x-8)-13x-7 | | 2x^2+8x+2y^2=0 | | 2(a-5-3)-5=3 | | 20+(-8x)-18=x | | -2x^2-3x+360=0 | | 6+x+6x=-22 | | 3x-5(2x+8)=9 | | 4x+3(x+2)=-17 | | x-31-(1.3x-31)=x | | 2t-11-8t=42 | | y-6=3(x-5) | | 2x^7-15x^5+12x^4=0 | | 3(-5)-y=1 |